Management of Lymphomas: A Case-Based Approach - Zain, Jasmine; Kwak, Larry W.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Adis, 2017)
This book will provide an overview of how to manage patients with lymphoma in the format of a series of engaging case studies. Lymphomas are cancers that originate in the lymphatic system. There are two main types of lymphoma: Hodgkin lymphoma and non-Hodgkin lymphoma. These lymphomas comprise various subtypes with prognosis and treatment depending on the stage and type of the cancer. Lymphoma is a major global health problem; non-Hodgkin lymphoma in particular is the tenth most common type of cancer worldwide. In response to this there have been a number of significant advances in the available treatment options for lymphoma with new breakthrough drugs being approved or registered for approval. In light of this, this case study book will be an extremely timely guide for all hematologists, oncologists, and healthcare professionals wishing to keep up-to-date with these recent developments. The format of this book is also particularly appealing as it offer readers a practical approach to the clinical management of patients with these conditions as suggested by leading physicians from the City of Hope National Medical Center in California, USA in an era of vast therapeutic development.
Overview of lymphoma -- Pathogenesis of lymphomas -- Classification of Hodgkin and non-Hodgkin lymphoma -- Case Study Section One: Indolent B-Cell Lymphomas -- Small B-cell lymphocytic lymphoma and chronic lymphocytic leukemia -- Follicular lymphoma -- Lymphoplasmacytic lymphoma in the era of next generation sequencing -- Case Study Section Two: Aggressive B-Cell Lymphomas -- Mantle cell lymphoma -- Burkitt lymphoma -- Diffuse large B-cell lymphoma -- Case Study Section Three: T-Cell Lymphomas -- Cutaneous T-cell lymphoma -- Systemic T-cell lymphoma -- Case Study Section Four: Hodgkin Lymphoma -- Hodgkin lymphoma -- Case Study Section Five: Lymphomas in Special Clinical Situations -- Acquired immunodeficiency syndrome-related lymphoma -- Central nervous system lymphoma -- Conclusion.
Keywords: Medicine; Cancer research; Hematology; Oncology; Pharmacotherapy; Medicine & Public Health; Hematology; Oncology; Cancer research; Pharmacotherapy